Manejo de residuos hospitalarios en el cantón Mocache - Ecuador 2017. - Santacruz Castro, David Absalon (2017)
The present investigation was carried out in the Mocache canton in order to evaluate the management of hospital waste, a census was applied to 46 direct and indirect stakeholders in the health centers, using the survey technique, as a dependent variable management was considered Of hospital, hazardous and non-hazardous waste and as an independent (collection, internal transport, storage, treatment, final disposal and personnel involved in waste management), the analytical and research method was applied to characterize solid hospital waste, Los Treatments of the data in the program spss 22 applying the t-Student, analysis of hierarchical conglomerates. During the year an average of 2877 people was reached, which generates 10654.9 kg / year of hospital waste, characterizing in common residues (52.2%), biological (18.5%) chemical (12.9%), Clippers (12.5%) and pharmaceuticals (3.9%); The analysis of the conglomerate allowed a 94.87% similarity between the biological and the chemical ones; A 89.74% similarity between the generation of short-pronged, pharmaceutical and common. With respect to compliance with current environmental regulations, 71% of the waste is in the range of conformities and 29% of nonconformities, therefore the level of uncertainty is good.